MODERN INFORMATION AND COMMUNICATIONTECHNOLOGIES AND THEIR USE IN TEACHINGCREATIVITY OF V.O. PELEVIN IN THE UNIVERSITY SYSTEM (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
At the end of the twentieth century. humanity has entered a stage of development, which is called the post-industrial or information society. But the judgment “We live in the age of information and communications” is not entirely correct, since both information and communications have always existed. Throughout the thousand-year history, human society has been accumulating knowledge and improving the ways of storing and processing information. First, writing spread, then the printing press, telephone, and television. With the entry of society into the age of computer technology, it became possible to process and present it more efficiently. Recently, modern Russian literature has been gaining momentum, and the study of Pelevin V.O.'s work with the use of information and communication technologies has become no less relevant.